2008
DOI: 10.1111/j.1423-0410.2008.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Extent of hepatitis E virus elimination is affected by stabilizers present in plasma products and pore size of nanofilters

Abstract: Background and ObjectiveTo investigate the physico-chemical properties of hepatitis E virus (HEV) with regard to inactivation/removal, we have studied four isolates with respect to sensitivity to heat during liquid/dry-heating as well as removal by nanofiltration. Materials and MethodsHepatitis E virus in an albumin solution or phosphatebuffered saline (PBS) was liquid-heated at 60 ° C for a preset time. HEV in a freezedried fibrinogen containing stabilizers was also dry-heated at 60 or 80 ° C for a preset tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Little is known on the physico-chemical properties of HEV with regard to inactivation/removal during industrial processes. Current data indicate that the sensitivity of HEV to heat vary depending on the heating conditions and the composition of the sample [18]. HEV particles are completely removed using 20 nm nanofilters [18].…”
Section: Basic Virologymentioning
confidence: 99%
“…Little is known on the physico-chemical properties of HEV with regard to inactivation/removal during industrial processes. Current data indicate that the sensitivity of HEV to heat vary depending on the heating conditions and the composition of the sample [18]. HEV particles are completely removed using 20 nm nanofilters [18].…”
Section: Basic Virologymentioning
confidence: 99%
“…By monitoring of seroconversion of pigs experimentally inoculated with an HEV GT3-containing liver suspension it was shown that incubation at 56°C for one hour did not affect infectivity, whereas the suspension was no longer infective after heating at 191°C (internal temperature of 71°C) or above 100°C each for five minutes [22]. Yunoki et al showed that proteins or magnesium may act as stabilizers, which can increase heat stability of HEV [23]. …”
Section: Introductionmentioning
confidence: 99%
“…However, neither kinetics of inactivation nor the influence of stabilisers such as those used in the production of clotting factors have been extensively investigated. Studies by a Japanese manufacturer of plasma products suggest a certain temperature resistance of HEV [223]. In these experiments the inactivation of HEV seemed to be limited to a factor of 2 log10 during pasteurisation of albumin (60 °C, 10 h).…”
Section: Blood Productsmentioning
confidence: 99%
“…Such filters are often used in the production of factor IX (FIX) and in part in the production of immunoglobulins or highly purified FVIII. Filtration of complex coagulation factors is only possible by using medium pore size filters (35-50 nm) that presumably will not remove HEV effectively [223] (PEI, unpublished data).…”
Section: Blood Productsmentioning
confidence: 99%